Correlation of Platelet Count, PDW, and MPV with Length of Stay in Children with Dengue Infection - Faqihudin, Fadli Rizal; Puspitasari, Metana; Jatmitko, Safari Wahtu; Dewi, Listiana Masyita (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The research aim to determine and analyze the correlation between platelet count, platelet distribution width, mean platelet volume and length of stay in children dengue virus patients. Methodology: This research used correlative observational study employed a cross-sectional design and included 48 children patients with dengue virus infection treated at PKU Muhammadiyah Sampangan Hospital, Surakarta. Platelet count, PDW, MPV, and LoS data were obtained from medical records. Statistical analysis to evaluate the correlation between these variables. Results: Results The study found platelet count (r = 0.28, p = 0.849), PDW (r = -0.110, p = 0.456), or MPV (r = 0.105, p = 0.477) no significant correlation with the length of stay. The result suggest that these platelet count, PDW, MPV are not acurate predictors of LoS in children dengue patients. Applications/Originality/Value: The platelet count, PDW, MPV are not reliable predictors the length of stay in children with dengue virus infection. This finding suggests for future studies, emphazie the need for a comprehensive clinical assessment rather than relying solely on platelet parameters when managing children dengue patients to predictors the length of stay in children with dengue virus infection and inform doctors in monitoring the course of dengue infection so that it is expected to reduce the incidence dengue infection in children.